Rare earths and minor elements chemical composition of internal layers of VA 13/2 (sample 237 KD) ferromanganese crusts - Ulrich von Stackelberg; Helmar Kunzendorf; Vesna Marchig; R Gwozdz (PANGAEA, 2022)
On the basis of the macroscopically visible layers, chemical analyses were carried out on various ferromanganese crust samples from VA 13/2 (station 237 KD) for minor elements and Rare Earths by neutron activation.